Design and test of a novel three-stage batch reactor for the accelerated carbonation of fresh concrete slurry waste - Svenja Vogt; Felix Brück; Harald Weigand (Results in Engineering, 2025)
Concrete slurry waste (CSW) accounts for approximately 1–4 % of total concrete production. It is generated from washing processes, surplus concrete, and surface treatments such as grinding. Due to its fresh state and high cement content, CSW has a significant CO2 uptake capacity. This study focuses on the design and test of a novel laboratory-scale reactor for the accelerated carbonation of fresh CSW. The reactor allows for time-resolved visualization of key process parameters. The slurry carbonation process was evaluated in batch mode using a model concrete slurry with a liquid-to-solid ratio of 100 and using reverse osmosis water as a reagent blank. Thermogravimetric-mass spectrometry analysis revealed CO2 uptake values of 15.64 wt.% and 17.65 wt.% in the model slurry after 30 min of carbonation treatment. Further carbonation-induced changes were determined by comparative analysis of the carbonated and native cement using X-ray diffractometry and X-ray fluorescence spectrometry. The reactor design and the results of the study are intended to optimize CO2 sequestration in CSW and thus contribute to sustainable waste management in the concrete industry.